Clinical Outcomes of Minimally Invasive Posterior Decompression for Lumbar Spinal Stenosis with Degenerative Spondylolisthesis. Issue 18 (15th September 2021) - Kobayashi, Yuto; Tamai, Koji; Toyoda, Hiromitsu; Terai, Hidetomi; Hoshino, Masatoshi; Suzuki, Akinobu; Takahashi, Shinji; Hori, Yusuke; Yabu, Akito; Nakamura, Hiroaki
Abstract : Study Design: Retrospective cohort study. Objective: To compare the clinical outcomes 5 years after minimally invasive posterior decompression for lumber spinal stenosis (LSS) between patients with and without degenerative spondylolisthesis (DS). Summary of Background Data: Indications for surgical procedures for patients with LSS and DS are still under investigation. Since minimally invasive surgery does not affect most anatomical structures, preoperative DS may not negatively affect the clinical outcomes of minimally invasive posterior decompression. Methods: Overall, 198 patients with LSS who underwent microendoscopic or microscopic decompression and were followed up for more than 5 years postoperatively were included in the present study. Patients who showed a segmental kyphosis >5° at the surgical level during flexion were treated with fusion surgery. However, other patients, including those with DS, were treated with posterior decompression. The patients were divided into two groups: the DS group included 82 patients with >3-mm slip and the non-DS group included 112 patients with ⩽3-mm slip or without slip. A mixed-effects model adjusted for age and sex was used to compare the improvements in the visual analog scale score for low-back pain and the Japanese Orthopaedic Association score of the two groups. For subgroup analysis (n = 53), the changes in the preoperative physical component summary and the mental component summary of Short Form-36 of the two groups at 5 years after surgery were evaluated. Results: There was no significant difference in the improvement of preoperative low-back pain visual analog scale score and Japanese Orthopaedic Association score 5 years after surgery between the two groups. Subgroup analysis showed no significant difference between the two groups in the improvement of preoperative physical component summary and mental component summary 5 years after surgery. Conclusion: After carefully eliminating patients with segmental instability, DS did not affect the clinical outcomes of minimally invasive decompression surgery. Level of Evidence: 3 Abstract : Minimally invasive decompression techniques, including microendoscopic laminectomy and endoscopic decompression, preserve paravertebral muscles and intervertebral joints. Degenerative spondylolisthesis is a common degenerative condition accompanied by lumbar spinal stenosis. Posterior decompression was effective for lumbar spinal stenosis patients with degenerative spondylolisthesis, with improvements in back pain, clinical symptoms, and quality of life.